Réponses

  • Omnes
  • Modérateur confirmé
2014-03-05T01:02:50+01:00
Salut,

A=4x-(3x+5)  
A = 4x - 3x - 5
A = x - 5

B=12x+(5-6x)      
B = 12x + 5 - 6x
B = 6x + 5

C=4x-(5-6x+9x2)-6x2    
C = 4x - 5 + 6x - 9x² - 6x²
C = 10x -5 - 15x²    

D=7x2-(9x-5)+(1-x2+x)      
D = 7x² - 9x + 5 + 1 - x² + x
D = 8x² +8x + 6

E=6(x+2)
E = 6x + 12

F=2x2+3 (4x-5)
F = 2x² + 12x - 15

Bonne soirée !

2014-03-05T01:08:50+01:00
A = 4x - (3x + 5)
A = 4x - 3x - 5
A = x - 5

B = 12x + (5 - 6x)
B = 12x + 5 - 6x
B = 6x + 5

C = 4x - (5 - 6x + 9 x 2) - 6 x 2
C = 4x - (5 - 6x + 18) - 12
C = 4x - 5 + 6x - 18 -12
C = 10x - 35

D = 7 x 2 - (9x - 5) + (1 - 2x + x)
D = 14 - 9x + 5 + 1 - x
D = -10x + 20

E = 6(x + 2)
E = 6x + 6 x 2
E = 6x + 12

F = 2 x 2+3(4x - 5)
F = 4 + 12x - 15
F = 12x -11

J'ai interprété tes équations comme j'ai pu car ce n'était pas forcément très explicite!